Knowledge Growth Measurement and Formulation for Enhancing Organizational Knowledge Capital - Al-Omari, Z.H. (2017)
This paper offers a conceptual framework for those details with the main component features for modeling knowledge growth. It has been contributing to important insights to future studies in the field of knowledge management to design a theoretical and operational model of knowledge growth in enhancing organizations' knowledge capital. This study approach considers three important issues: such as the categories of knowledge for measurement, the elicitation and measurement of organizational knowledge growth by designing a knowledge growth elicitation and measurement tool (KGEMT), and formulating a model for knowledge growth measurement. The review and analyses show that knowledge growth measurement and elicitation is an active research spanning from the concepts that include the stages of knowledge growth; evolutionary theories that involve continuous organizational learning; knowledge growth elicitation to capture the component features of a knowledge growth process from users formulation of knowledge growth; and formation of knowledge capital. From these findings, the study conceptualized a framework for modeling and measuring organizational knowledge growth. The study developed the knowledge elicitation and measurement tool, which captures work episodes of knowledge workers in organizations; organizing the knowledge into explicit and tacit knowledge, and enumerating such knowledge to produce a measure of knowledge growth within the duration of measurement. While the results of the enumeration may be subject to criticism, the tool does provide an indication of the knowledge growth in organizations. © 2014 Springer Science+Business Media New York.